ADOPSI SISTEM PERTANIAN BERKELANJUTAN (KASUS PETANI SAYURAN DAN BUAH DESA NEGLASARI, DRAMAGA, BOGOR) - Euriga, Epsi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
Sustainable Agriculture System (SAS) is an innovative technology that could overcome the problems related to environmental sustainability. Farmers in Neglasari village, Dramaga has not entirely adopted the SAS innovation including integrated pest management, balanced fertilization, crop rotation, and tillage as recommended. This study aims to: (1) To analyse factors that influencing farmer perception toward SAS implementation. (2) To analyse the factors that influencing farmer attitude toward SPB. (3) Analyse the factors that influencing SAS adoption. The research conducted with survey method that involved 31 fruit and vegetable farmers. The results showed that age had significantly negative effect toward perception. Information from the extension and the type of participation had significantly positive effect toward perception. Type of participation had significantly positively effect toward the attitudes of farmers towards sustainable agriculture systems. Age and perceptions of sustainable farming systems had significantly positive effect toward the adoption of sustainable farming systems, while the extension information and the type of participation had significantly negative effect on the adoption of sustainable farming systems.